Standardising Cornish: The politics of a new minority language - Dave Sayers (Language Problems & Language Planning, 2012)
The last recorded native speaker of the Cornish language died in 1777. Since the nineteenth century, amateur scholars have made separate attempts to reconstruct its written remains, each creating a different orthography. Later, following recognition under the European Charter for Regional or Minority Languages in 2002, Cornish gained new status. However, with government support came the governmental framework of “New Public Management”, which emphasises quantifiable outcomes to measure performance. This built implicit pressure towards finding a single standard orthography, for greatest efficiency. There followed a six- year debate among supporters of the different orthographies, usually quite heated, about which should prevail. This debate exemplified the importance of standardisation for minority languages, but its ultimate conclusion saw all sides giving way, and expediency, not ideology, prevailing. It also showed that standardisation was not imposed explicitly within language policy, but emerged during the language planning process.